Treatment outcome after radiochemotherapy in anal cancer patients staged with 18F-FDG-PET-CT. (September 2020) - Braun, L.H.; Reinert, C.P.; Zips, D.; Nikolaou, K.; Pfannenberg, C.; Gani, C.
Highlights: Long-term treatment outcomes of PET staged anal cancer patients after radiochemotherapy are presented. PET data correlated with primary tumor and nodal stage. Outcome appears promising compared with the literature. Abstract: Background: Anal cancer (AC) is a malignancy with increasing incidence and commonly treated with radiochemotherapy. Positron-emission tomography-computed tomography (PET/CT) has been shown to improve treatment outcome in various oncological diseases, however, for AC long-term outcome data is sparse. The aim of the present study is therefore to report outcomes in our cohort of PET/CT staged AC patients treated with radiochemotherapy. Methods: Patients with AC who were treated with radiochemotherapy in curative intent were included in this retrospective study if a PET/CT scan was performed pre-therapeutically. Information from PET/CT was considered for nodal and primary target volume definition. Radiotherapy dose to the primary tumor was 50–66 Gy and concomitant chemotherapy included 5-fluorouracil and mitomycin-C. The uptake of 18 F-fluorodeoxyglucose (FDG) was quantified using 50%-isocontour volumes of interests (VOIs) and measuring the standardized uptake value (SUV) and the metabolic tumor volume (MTV). 18 F-FDG uptake was correlated with baseline clinical parameters and long-term oncological outcome. Survival estimates were determined according to Kaplan-Meier. Results: A total of 60 patients were included in this study. Estimates for three-year overall survival (OS) and disease free survival (DFS) were 94.5% and 80%. Five patients developed local (n = 2) or locoregional and local (n = 3) failure. Baseline PET/CT related parameters correlated with primary tumor stage, nodal stage and tumor grading. DFS was independent of T-stage, N-stage and baseline 18 F-FDG-uptake. Conclusion: In this cohort of PET/CT staged AC patients, excellent outcomes for DFS were seen. PET-based markers of tumor burden correlate with local stage of AC, however, are not of prognostic relevance for disease-free survival.